Xénophobie et intolérance en Bolivie : Orient versus Occident - Jean-Pierre Lavaud (Nuevo mundo - Mundos Nuevos, 2010)
Recent surveys on the issue of racism in Bolivia confirm the cliché that the inhabitants of the department and the city of Santa Cruz are the most racist of the country. However when the questions that are asked are no longer on a general appreciation of the attitudes of groups of people, but how the discrimination suffered were felt by the respondents, the trend is reversed. After all, Santa Cruz appears as a region relatively less xenophobic and more open than others, including La Paz.